An inherited FGFR2 mutation increased osteogenesis gene expression and result in Crouzon syndrome - Jiayan Fan; Yinwei Li; Renbing Jia; Xianqun Fan (BMC, 2018)
Abstract Background FGFR2 encodes a fibroblast growth factor receptor whose mutations are responsible for the Crouzon syndrome, involving craniosynostosis and facial dysostosis with shallow orbits. However, few reports are available quantifying the orbital volume of Crouzon syndrome and there was little direct evidence to show FGFR2 mutation actually influencing orbital morphology. Methods Ten Crouzon syndrome patients underwent a standard ophthalmologic assessment. Morphology study was carried out based on 3-dimensional computed tomography scan to calculate orbital volume. Genomic DNA was extracted from peripheral blood leukocytes of the patients and genomic screening of FGFR2. A three-dimensional computer model was used to analyse the structural positioning of the mutation site that was predicted possible impact on functional of FGFR2 protein. Real-time PCR was performed to analyse the expression of bone maker gene. Results We describe a FGFR2 mutation (p.G338R, c.1012G > C) in a Chinese family with Crouzon syndrome. Computational analysis showed the mutate protein obviously changes in the local spatial structure compared with wild-type FGFR2. The expression of osteocalcin and alkaline phosphatase two osteoblast specific genes significantly increased in orbital bone directly from patient compared to normal individual, which may lead to facial dysostosis. This is compatible with the shallow and round orbits in our Crouzon syndrome patient. Conclusions Our study further identified G338R FGFR2 mutation (c1012G > C) lead to inherited Crouzon syndrome. Thus, early intervention, both medically and surgically, as well as disciplined by a multiple interdisciplinary teams are crucial to the management of this disorder.